MORAL IDEAL-BASED QUR`AN INTERPRETATION ACCORDING TO SHĀṬIBĪ’S CONCEPT OF MAQĀṢID AL-SHARĪ’AH - Wardani Wardani; Majed Fawzi Abu Ghazalah; Mazlan Ibrahim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
Many kinds of research conducted so far reported that scripture unfortunately has been approached only from its legal doctrines. They tend to corrupt moral aspects as the very essential contents of scripture toward which God projects His doctrines. The trends of Quranic interpretation studies have also been limited to study legal or theological approaches neglecting the importance of its underlying moral ideals. To fill the gap, this article is aimed to offer a model of Quran interpretation based on its moral ideals, by focusing on elaborating Shāṭibī’s concept of maqāṣid al-sharī’ah (the goals of sharīa). It will deal firstly with extracting moral values underlying this concept, secondly, by employing Fazlur Rahman’s theory of distinction between legal-specific and moral ideals of Quranic teachings, it deals with constructing the models of Qur`an interpretation. The moral issues will be approached from a philosophical approach and the interpretation issues will be elaborated employing a hermeneutical perspective. Results reveal that the moral ideal-based Qur`an interpretation can be constructed based on the value-system of the maqāṣid, such as the theological-transcendental, theological pragmatic, and instrumentalist values. The interpretation can be projected both to an ethico-historical understanding of verses by connecting a historical context, literary context, and values and to an ethico-contextual approach by connecting a present situation, literary context, and values.